Academic performance of students in different type of schools: an exploratory study based on demographic factors, a case study in Kota Bharu / Nor Fatihah Binti Abd Razak ...[et al.] - Abd Razak, Nor Fatihah; Norshahidi, Nur Dalila; Che Yusof, Nur Syaliza Hanim; Abdul Malik, Mohd Azry (Unit Penerbitan UiTM Kelantan, 2018)
In Malaysia, there are several debates among society regarding the different academic performance between coeducational and single-gender school. Students from single-gender schools seem to perform better compared to students from coeducational schools by referring to their examination results. Since, there are less study conducted pertaining to this issue, this study was conducted to identify the influence factors of academic performance of students from single-gender and coeducational schools in Kota Bharu, Kelantan. This study was using secondary data where sample size was 414 samples. The Two Independent Sample T-test and Kruskal Wallis test were applied to examine the objectives. As a conclusion, there are significant difference in academic performance of students between single gender and coeducational schools. Meanwhile, the academic performance for male students (single gender) much better compared to mixed gender (coeducational). Female students in single gender schools excel in their academic performances compared to male students (single gender) and mixed (coeducational). This study recommend to add more variables related to the study and increase the number of samples or schools involved.